TINJAUAN PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) (STUDI KASUS: PEMBANGUNAN GEDUNG TELKOMSEL PEKANBARU) - Taufik, Hendra; Trikomara, Rian; Efpridawati, Nora (Proceedings ACES (Annual Civil Engineering Seminar), 2015)
The growth of economy in Pekanbaru is taking the private sector to participate in thedevelopment of Pekanbaru city. One of the example is the construction of Network Building ofPekanbaru. This project is an interesting project to observe due to the stature of Telkomsel as agiant company that has worked on the field of construction for over than 50 years andemploying 100 works which are having high risk of work accident. Therefor it is necessary toconduct a research about the evaluation of SMK3 application on those project in accordancewith PP N0.50 Tahun 2012 thus the work accident can be reduced to minimum. The methodused in this research is quantitative method, Univariat analysis and qualitative descriptive.Questioner are distributed to 19 respondent for staffs and 108 respondent for workers. Thisresearch yields the results of evaluation for the level of success for SMK3 application at77,01% which is classified in category two with the range of accomplishment at 60-84%meaning good achievement. As for the success level of SMK3 Audit result, the value isobtained at 84,34% and classified in good application with 24 minor incompatibility. Thefactors that affect the workers in the application of SMK3 is psychology factor and thecondition of project environment.Kata kunci: Audit, Evaluation, Network Building, SMK3, Telkomsel